2019
DOI: 10.1002/pssb.201900199
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Tuning Through Irradiation Defects in CH3NH3PbI3 Perovskites

Abstract: Defect engineering is applied to hybrid (CH 3 NH 3 )PbI 3 organic-inorganic perovskites. These materials have become one of the most promising lowcost alternatives to traditional semiconductors in the field of photovoltaics and light emitting devices. Here Helium ion irradiation at low energy has been used as a tool for the controlled introduction of point defects in both single crystals and polycrystalline thin films. The irradiation defects modify the opto-electronic properties as probed using photoluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The low-energy asymmetry in PL emission is related to presence of bound excitons and shallow energy levels by iodine interstitials defects. [36,37] Figure 5b shows the semilog scale temperature dependent PL spectra of demixed stage measured at high power-density (840 mW cm −2 ). For demixed stage dynamics, first sample was illuminated at high power (840 mW cm −2 ) at room temperature to create phase segregated domains and then cooled down to 10 K under continuous photoexcitation.…”
Section: Low-temperature Dynamics and Role Of Exciton-phonon Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-energy asymmetry in PL emission is related to presence of bound excitons and shallow energy levels by iodine interstitials defects. [36,37] Figure 5b shows the semilog scale temperature dependent PL spectra of demixed stage measured at high power-density (840 mW cm −2 ). For demixed stage dynamics, first sample was illuminated at high power (840 mW cm −2 ) at room temperature to create phase segregated domains and then cooled down to 10 K under continuous photoexcitation.…”
Section: Low-temperature Dynamics and Role Of Exciton-phonon Couplingmentioning
confidence: 99%
“…5 (a) shows the temperature-dependent PL spectra of mixed stage (parent phase), on a semi-logarithmic scale measured at low excitation power-density (< 1 mW/cm 2 ) and exhibits a single emission peak with low energy asymmetry at low-temperature (10 K). The lowenergy asymmetry in PL emission is related to presence of bound excitons and shallow energy levels by iodine interstitials defects [37,38]. Fig 5 (b) shows the semi-log scale temperature dependent PL spectra of demixed stage measured at high power-density (840 mW/cm 2 ).…”
Section: Low-temperature Dynamics and Role Of Exciton-phonon Couplingmentioning
confidence: 99%
“…We have introduced on purpose different defect concentrations into TC‐MHP polycrystalline thin films, of composition (MA 0.17 FA 0.83 ) 0.95 Cs 0.05 Pb(I 0.83 Br 0.17 ) 3 , with proton irradiation at 1 MeV and different fluences from 10 13 cm −2 to 5 × 10 15 cm −2 . Contrary to usual semiconductors, where irradiation defects quench the luminescence very efficiently, it was already observed that hybrid perovskite samples, both in single crystals and polycrystalline thin films, present high radiation hardness under Helium ion irradiation using low energy at 30 keV [ 22 ] or proton irradiation at 50 keV. [ 23 ] We estimated, for instance, that these compounds were about 10 5 times more radiation‐hard than crystalline silicon.…”
Section: Irradiation Effect On Mixed‐halide Perovskitementioning
confidence: 99%
“…Irradiation of CsPbBr 3 and MAPbI 3 (MA + = CH 3 NH 3+$_3^ + $) halide perovskites with such doses of 30 keV Ga + or He + ions leads to the formation of defect serving as radiative recombination centers. [ 28–30 ] The irradiation with meV ion beams leads to the increase in the emission of MAPbBr 3 . [ 31 ] Such behavior could be explained by the well‐known defect tolerance of these materials [ 32 ] which gives hope for the possibility of careful modulation of excitonic properties by FIB.…”
Section: Introductionmentioning
confidence: 99%